Academic Ethical Awareness among Undergraduate Nursing Students of a Private University in Nigeria: A Cross-Sectional Descriptive Study - Taiwo Omotayo Dosumu RN, MSc; Oluwaseyi Isaiah Olabisi PhD; Mathew Idowu Olatubi PhD; Grace Olayanju RN, MSc; Deborah Okedele RN, MSc; Chizoma Millicent Ndikom PhD (SAGE Publishing, 2024)
Introduction Academic ethical awareness is a crucial prerequisite for practice, serving as the cornerstone for a professional demeanor in clinical settings and ensuring future adherence to nursing ethics. Objectives This study assessed academic ethical awareness as well as its related characteristics among undergraduate Nursing students of a private university in Nigeria. Methods A descriptive cross-sectional research design was utilized. The study was conducted among undergraduate nursing students of a private university in Nigeria. A convenience sample of 158 nursing students from 300 level to 500 level voluntarily participated in this study. Data were collected using the Academic Ethical Awareness Questionnaire and descriptive statistics, mean and standard deviation were employed to analysis the data collected. Results The mean age of nursing students was 21.1. Majority of the respondents were females, Christians and claimed average financial status with 87%, 94%, and 68%, respectively. Nursing students demonstrated moderate academic ethical awareness (69.5%), a mean score of 3.68 ± 0.81. They knew that revealing patient information in public places of the hospital, disregarding, slandering, or making fun of patients in face-to-face interaction, and having someone else attend class as a substitute were unethical behaviors with mean scores of 3.96, 3.90, 3.88, and 3.88, respectively. Academic ethical awareness was low for submitting cut and paste report, not paying attention in class and being late to class, with mean scores 1.81, 2.05, and 2.80, respectively. Gender, level of study, and satisfaction with Nursing as a course of choice are significant determinant of ethical academic awareness with P value of .018, .005, and .011, respectively. Conclusion Nursing students assessed demonstrated moderate academic ethical awareness. Improved instruction is required regarding the value of appropriate classroom behavior and emphasis on the implications of plagiarism in practice.